Akupresur Titik Perikardium 6 pada Ibu Hamil Trimester I - Tanjung, Wiwi Wardani; Nasution, Eva Yusnita (Jurnal Pengabdian Masyarakat Aufa (JPMA), 2021)
Nausea and vomiting usually occur in the morning, but some occur at any time of the day and occur as a result of changes in the endocrine system that occur during pregnancy, especially the increase in the hormone hCG in pregnancy. Data in Indonesia 50% to 80% of pregnant women experience nausea and vomiting and approximately 5% of pregnant women require treatment for fluid replacement and correction of electrolyte imbalances. One of the non-pharmacological therapies to treat nausea and vomiting is acupressure at the point of the Pericardium 6 (P6). The stimulatory effect at this point can increase the release of beta-endorphins in the pituitary and adrenocorticotropic (ACTH) along the chemoreceptor tringger zone (CTZ) which can inhibit the vomiting center. Based on the results of interviews conducted with pregnant women, they said that they had never heard the term pericardium 6 and also did not know the benefits of this action. Therefore, it is necessary to increase knowledge in an effort to reduce nausea and vomiting in pregnant women in the first trimester. Activities carried out in this community service are acupressure at the point of pericardium 6 in trimester I pregnant women. This activity aims to reduce the intensity of nausea and vomiting experienced by the mother. trimester I pregnancy. The result of this activity is that there is a change in the intensity of nausea and vomiting that is felt by trimester I pregnant women after acupressure is carried out at the pericardium point 6